Incidence of Surgical Site Infections and Acute Kidney Injuries After Topical Antibiotic Powder Application in Orthopaedic Trauma Surgery. Issue 10 (October 2021) - Balabanova, Alla; Chu, Xiangquan; Chambers, Lori; Mauffrey, Cyril; Parry, Joshua A.
Abstract : Objectives: To compare the incidence of deep surgical site infections (SSI) and acute kidney injuries (AKI) in patients who did and did not receive topical antibiotics during the open treatment of fractures. Design: Retrospective comparative cohort. Setting: Level 1 trauma center. Patients/Participants: Three hundred ninety-six patients undergoing open fixation of fractures. Intervention: The topical antibiotic group included 78 (20%) patients. Vancomycin only was used in 28 (7%) patients with the median dose (interquartile range) of 1 g (1–2 g) and vancomycin/tobramycin was used in 48 (12%) patients with a median dose (interquartile range) of 2 g (1–2 g)/1.2 g (1.2–1.2 g). Main Outcome Measurements: Deep SSI requiring debridement and AKI (>50% increase in creatinine compared with preoperative level). Results: There was no detectable difference in SSI between the topical antibiotic and control groups (13% vs. 10%, odds ratio (OR) 1.3, 95% confidence interval (CI) 0.6 to 2.9). Variables associated with SSI on multivariate analysis included open fracture (OR 3.2, CI 1.5 to 6.5) and an American Society of Anesthesiologists classification of >2 (OR 2.7, CI 1.3 to 5.3). There was no detectable difference in AKI between the topical antibiotic and control groups (1 (2%) vs. 7 (5%); OR 0.3, CI 0.04 to 3). Conclusion: There was no detectable difference, with wide confidence intervals, in SSI and AKI between the topical antibiotic and control groups. Further studies need to be conducted to evaluate the relationship between topical antibiotics and clinical outcomes in orthopaedic trauma surgery. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.